Physical exercise and goal attainment after shunt surgery in idiopathic normal pressure hydrocephalus: a randomised clinical trial - Johanna Rydja (BMC, 2021)
Abstract Background Rehabilitation in iNPH is suggested to be an important factor to improve patients’ functions but there are lack of clinical trials evaluating the effect of rehabilitation interventions after shunt surgery in iNPH. The objective of this study was to evaluate the effect of a physical exercise programme and goal attainment for patients with idiopathic normal pressure hydrocephalus (iNPH) after surgery compared to a control group. Methods This was a dual centre randomised controlled trial with assessor blinding, intention-to-treat (ITT) and per protocol (PP) analysis. Individuals diagnosed with iNPH scheduled to undergo shunt surgery at the Linköping University Hospital in Linköping and Sahlgrenska University Hospital in Gothenburg, Sweden were consecutively eligible for inclusion. Inclusion was conducted between January 2016 and June 2018. The patients were randomised 1:1 using sequentially numbered sealed envelopes to receive either written exercise information (control group) or written information and an additional supervised high-intensity, functional exercise programme (HIFE) executed twice weekly over 12 weeks (exercise group). Preoperatively, the patients set individual goals. The primary outcome was change from baseline in the total iNPH scale score at the post-intervention follow-up. Secondary outcomes were goal attainment, and change in the separate scores of gait, balance, neuropsychology and continence and in the total score after 6 months. Results In total, 127 participants were randomised to the exercise group (n = 62) and to the control group (n = 65). In the ITT population (exercise group, n = 50; control group, n = 59), there were no between-group differences in the primary outcome, but the attrition rate in the exercise group was high. The exercise group improved more than the control group in the balance domain scores after 6 months. Post-intervention, the PP exercise population achieved their set goals to a greater extent than the controls. Conclusions An additional effect of the 12-week HIFE-programme on the overall improvement according to the iNPH-scale after shunt surgery in iNPH was not shown. This could be due to high attrition rate. However, the long-term effect on balance and higher goal achievement indicate beneficial influences of supervised physical exercise. Trial registration clinicaltrials.gov, NCT02659111. Registered 20 January 2016, https://clinicaltrials.gov/ct2/show/NCT02659111